Witnessing the quantumness of a system by observing only its classical features. (December 2017) - Marletto, C.; Vedral, V.
Abstract A central problem in fundamental physics is to witness the non-classicality of systems whose dynamics is not completely specified. For example, this arises in testing predictions that a macroscopic system, such as a living system, obeys quantum theory. Notoriously, also, it has been claimed that witnessing non-classicality in the gravitational field is practically impossible. Here, we propose a thought experiment that witnesses the non-classicality of a physical system by probing it with a qubit, without having to assume any specific dynamics on the physical system. Remarkably, this experiment does not require any quantum control of the system, involving only measuring a single classical observable on it. That non-classicality of a system can be established indirectly, by coupling it to a qubit, opens up exciting possibilities, for example, that quantum gravitational effects might be witnessed in the lab. Quantum mechanics: witnessing quantumness by observing only classical features Witnessing quantum-like features of systems whose dynamics is not completely specified is a central problem in physics. For example, one wants to test whether a macroscopic system, such as a living system, obeys quantum theory, or whether the gravitational field displays quantum effects. Here, scientists for UK propose a thought experiment that witnesses non-classicality of a physical system by probing it with a qubit, without having to assume any specific dynamics on the physical system. This experiment does not require any quantum control of the system, involving only measuring a single classical observable on it. That non-classicality of a system can be established indirectly, by coupling it to a qubit, opens up exciting possibilities, for example that quantum gravitational effects might be witnessed in the lab.